2018
DOI: 10.1111/cla.12361
|View full text |Cite
|
Sign up to set email alerts
|

Unparalleled disjunction or unexpected relationships? Molecular phylogeny and biogeography of Melanopsidae (Caenogastropoda: Cerithioidea), with the description of a new family and a new genus from the ancient continent Zealandia

Abstract: Melanopsidae are an important component of the freshwater fauna of the subtropical to temperate regions of the Western Palaearctic and also are reported from Zealandia, representing an unparalleled disjunction among a group of freshwater animals. We sequenced markers for species of all constituent genera covering the entire range of the group. Our phylogenetic analyses indicate that Melanopsidae are only monophyletic when excluding Holandriana from the Balkans, which was found to be more closely related to Ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…In total, 289 COI barcode sequences were obtained and uploaded in the "GEOFM" BOLD project, representing 33 species from 24 molluscan genera from 10 families. Prior to the present study, there were 47 freshwater molluscs COI barcode sequences available in the BOLD Systems (from the study area) including 11 sequences from an unpublished project within the "DNAqua-Net" COST Action (Leese et al 2016 (Grego et al 2017, Grego et al 2020) and a single sequence of Melanopsis mingrelica (Neiber and Glaubrecht 2019) and Radix euphratica (Aksenova et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 289 COI barcode sequences were obtained and uploaded in the "GEOFM" BOLD project, representing 33 species from 24 molluscan genera from 10 families. Prior to the present study, there were 47 freshwater molluscs COI barcode sequences available in the BOLD Systems (from the study area) including 11 sequences from an unpublished project within the "DNAqua-Net" COST Action (Leese et al 2016 (Grego et al 2017, Grego et al 2020) and a single sequence of Melanopsis mingrelica (Neiber and Glaubrecht 2019) and Radix euphratica (Aksenova et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The check-list of freshwater molluscs species for the South Caucasus or any separate country within it is more than 50 years old and completely outdated (Zhadin 1952, Javelidze 1973, Akramowski 1976. While a number of papers have appeared during the last three decades providing information on the taxonomy and systematics of separate taxa (given below), only three articles have been published reporting the field research-based inventory results of all freshwater molluscs of a particular area: for Sevan Lake in Armenia (Mashkova et al 2018), Javakheti region of Georgia -Bikashvili et al ( 2021) and Kazbegi Municipality in Georgia - Neiber et al (2021). Thus, it is clear that the current knowledge of freshwater molluscs species diversity and distribution in the South Caucasus region remains far from being comprehensive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superfamily Cerithioidea currently includes 21 families (Bouchet et al. 2017 ; Neiber and Glaubrecht 2019d ), nine of which inhabit freshwater environments: Amphimelaniidae, Hemisinidae, Melanopsidae, Pachychilidae, Paludomidae, Pleuroceridae, Semisulcospiridae, Thiaridae, and Zemelanopsidae (Campbell 2019 ; Glaubrecht and Neiber 2019a , 2019b ; Neiber and Glaubrecht 2019a , 2019b , 2019c , 2019d ; Strong and Lydeard 2019 ). Initially, most of the freshwater species in the superfamily Cerithioidea were placed in the family Melaniidae and the genus Melania (Neiber and Glaubrecht 2019b ).…”
mentioning
confidence: 99%
“…With the development of molecular systematics, it was found that the cerithioidean freshwater taxa were not monophyletic, and the taxonomic positions of some cerithioidean families are still unclear (Strong et al. 2011 ; Neiber and Glaubrecht 2019d ). Tarebia granifera (Lamarck, 1816) is an invasive species native to South and Southeast Asia and several Western Pacific Islands.…”
mentioning
confidence: 99%